Conflict Management Styles, Workplace Incivility and Organizational Commitment of Teachers in Region XI: an Explanatory Sequential Design - P. Lutog, Marevic Jean; O. Aoanan, Grace (The Future of Education Journal, 2024)
Organizational commitment of teachers has been a prevalent issue in education which stem from different underlying factors at present.  This explanatory sequential mixed-method study aimed to assess and examine the influence of conflict management style and workplace incivility toward organizational commitment of Region XI junior high school teachers. The respondents were from large and implementing schools of different school divisions for the quantitative phase. For the qualitative phase, the participants were purposively selected for the in-depth interview and focus group discussions. A validated and adapted survey questionnaire along with the interview guide were utilized in the gathering of data. For the results, regression analysis and thematic analysis were employed to interpret the data collected. The quantitative findings indicated that conflict management styles were high, workplace incivility is seldom observed, and organizational commitment is oftentimes manifested. Additionally, both conflict management styles and workplace incivility significantly influenced and predicted organizational commitment of junior high school teachers. In the qualitative phase, the results corroborated the quantitative findings, affirming the high ratings of conflict management styles and organizational commitment, and the low rating of workplace incivility. The integration of data revealed confirmation-connection between the two sets of results. The findings of the study are relevant to maintain the organizational commitment of teachers in the department.